Ethnography for the Internet embedded, embodied and everyday - Hine, Christine (London, UK Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc, 2015)
"The internet has become embedded into our daily lives, no longer an esoteric phenomenon, but instead an unremarkable way of carrying out our interactions with one another. Online and offline are interwoven in everyday experience. Using the internet has become accepted as a way of being present in the world, rather than a means of accessing some discrete virtual domain. Ethnographers of these contemporary internet-infused societies consequently find themselves facing serious methodological dilemmas: where should they go, what should they do there and how can they acquire robust knowledge about what people do in, through and with the internet? This book presents an overview of the challenges faced by ethnographers who wish to understand activities that involve the internet. Suitable for both new and experienced ethnographers, it explores both methodological principles and practical strategies for coming to terms with the definition of field sites, the connections between online and offline and the changing nature of embodied experience. Examples are drawn from a wide range of settings, including ethnographies of scientific institutions, television and social media, and locally-based gift-giving networks"-- Provided by publisher.
1. Introduction -- 2. The E3 internet: the embedded, embodied, everyday internet -- 3. Ethnographic strategies for the embedded, embodied, everyday internet -- 4. Observing and experiencing online/offline connections -- 5. Connective ethnography in complex institutional landscapes -- 6. The internet in ethnographies of the everyday.
Includes bibliographical references (pages 197-212) and index.
Keywords: Internet -- Social aspects; Internet users; Ethnology -- Research -- Methodology